Analisa Performa Bisnis di Desa Wisata Kandri Semarang Berdasarkan Karakteristik Responden - syaiful ade septemuryantoro (PolimdoSains, 2021)
Tourism village as an alternative tourism for tourists who can provide a source of income. The main problem is the difficulty of managing and planning finances. The purpose of the research is to test business performance based on the characteristics of the respondents which including gender, age, and level of education. The total sample taken is 50 respondents. Data is retrieved through questionnaire. The method of analysis used is a different test one way ANOVA analysis with a significance level of 5% . Test results show that there is no significant difference in business performance based on gender, age or level of education.